Peran Media Sosial dalam Penyampaian Aspirasi Masyarakat untuk Perubahan yang Lebih Baik - Hafizd, Jefik; Nurfalah, Fika Siti; Ramadhan, Mohamad Arya Pradana; Kaerudin, Pipin; Elok, Kharisma (CV. Strata Persada Academia, 2023)
The advancement of technology has made access to information easier and faster. With the development of technology, social media has emerged as a quick and easily accessible platform for conveying information. Social media can be used to access a wide range of content. This research investigates the role of social media in conveying the aspirations of the public using a qualitative descriptive research method. Data sources were derived from interviews and a literature review of relevant regulations, journals, and other sources. This study examines how social media plays a role in conveying the aspirations of the public. The findings indicate that in the management of a democratic government, social media can be used to voice aspirations. Social media users can express their aspirations through platforms such as Instagram, Facebook, Twitter, TikTok, and other social media outlets. The public has the ability to express their aspirations through videos or other formats shared on social media. Information from the public can quickly disseminate and be accessed by various individuals. Trending information typically receives a rapid response from authorities, who then work to provide solutions and address those aspirations.